2020
DOI: 10.1177/0963689720913256
|View full text |Cite
|
Sign up to set email alerts
|

Islet Transplantation to the Anterior Chamber of the Eye—A Future Treatment Option for Insulin-Deficient Type-2 Diabetics? A Case Report from a Nonhuman Type-2 Diabetic Primate

Abstract: Replacement of the insulin-secreting beta cells through transplantation of pancreatic islets to the liver is a promising treatment for type-1 diabetes. However, low oxygen tension, shear stress, and the induction of inflammation lead to significant islet dysfunction and loss. The anterior chamber of the eye (ACE) has gained considerable interest and represents an alternative therapeutic islet transplantation site because of its accessibility, high oxygen tension, and immune-privileged milieu. We have previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Moreover, our studies demonstrated immunosuppressionfree, long-term survival of intraocular islet allografts in mouse and nonhuman primate models 27,28 . These studies provided evidence for local and peripheral immune regulation consistent with donor-specific tolerance that promoted the survival of additional islet grafts from the same donors 27 .…”
mentioning
confidence: 55%
“…Moreover, our studies demonstrated immunosuppressionfree, long-term survival of intraocular islet allografts in mouse and nonhuman primate models 27,28 . These studies provided evidence for local and peripheral immune regulation consistent with donor-specific tolerance that promoted the survival of additional islet grafts from the same donors 27 .…”
mentioning
confidence: 55%
“…The transduced islets were verified under a fluorescence microscope (SP8, Leica, Germany) for EGFP fluorescence before transplantation. A small self-sealing incision was made on the clear cornea, 3 mm away from the cornea-sclera junction, and around 50 islets were transplanted into the ACE of each monkey as previously described 8 . A 0.5 ml bolus dose of sub-conjunctival dexamethasone (4 mg/ml; DBL, Pfizer, New York, USA) injection was given immediately after the transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, the ACE can be used to monitor auto-immune response in islet cells, while simultaneously monitoring the morphology of transplanted islet. A study by Tun et al demonstrated that total of 12,000 islets (1500 IEQ/kg) transplantation in a left eye site in cynomolgus monkeys induced with early T2D through a high fat diet was able to delay progression of T2D and related complications (72). The authors observed that three months after immunosuppressants were withdrawn, the primates were still able to control hyperglycemia, indicating an acquired immune privilege/tolerant status for the transplanted islets.…”
Section: Anterior Eye Chamber Transplantation Sitementioning
confidence: 99%